Neuropathology and diagnostics in food animals - Nietfeld, Jerome C. (My University, 2012)
Diseases of the central nervous system are relatively common in food animals. Potential causes include infectious agents, nutritional deficiencies, metabolic disorders, genetic defects, toxins, and idiopathic causes. Food animals are frequently raised in large groups, there is often human and animal traffic between groups, and large numbers of animals are often fed the same ration. This makes it important to obtain an accurate etiological diagnosis as soon as possible so that treatment can be initiated and to limit the spread of infectious agents and toxins. In all disease situations, an antemortem diagnosis is preferable to a postmortem one because it allows for possible treatment of affected individuals, but that is not always possible and determining the correct etiologic diagnosis often depends on a thorough postmortem examination and collection of samples. Critical components for obtaining a successful diagnosis are as complete a history as possible, a thorough examination of affected and unaffected animals and their surroundings, a thorough necropsy and collection of the appropriate diagnostic samples, and accurate interpretation of the findings. The goals of this article are to review some of the steps and procedures necessary to collect the necessary information, to briefly describe a few techniques for examination of the central nervous system, and to review the gross pathology of conditions likely to be encountered in a food animal practice.
Keywords: Neuropathology; Diagnostics; Cattle; Sheep; Pigs; Food animals